Experimental and clinical usefulness of crossmodal paradigms in psychiatry: an illustration from emotional processing in alcohol-dependence - Maurage, Pierre; Campanella, Salvatore (Frontiers in Human Neuroscience, 2013)
Cross-modal processing (i.e., the construction of a unified representation stemming from distinct sensorial modalities inputs) constitutes a crucial ability in humans’ everyday life. It has been extensively explored at cognitive and cerebral levels during the last decade among healthy controls. Paradoxically however, and while difficulties to perform this integrative process have been suggested in a large range of psychopathological states (e.g., schizophrenia and autism), these cross-modal paradigms have been very rarely used in the exploration of psychiatric populations. The main aim of the present paper is thus to underline the experimental and clinical usefulness of exploring cross-modal processes in psychiatry. We will illustrate this proposal by means of the recent data obtained in the cross-modal exploration of emotional alterations in alcohol-dependence. Indeed, emotional decoding impairments might have a role in the development and maintenance of alcohol-dependence, and have been extensively investigated by means of experiments using separated visual or auditory stimulations. Besides these unimodal explorations, we have recently conducted several studies using audio-visual cross-modal paradigms, which has allowed us to improve the ecological validity of the unimodal experimental designs and to offer new insights on the emotional alterations among alcohol-dependent individuals. We will show how these preliminary results can be extended to develop a coherent and ambitious research program using cross-modal designs in various psychiatric populations and sensory modalities. We will finally end the paper by underlining the various potential clinical applications and the fundamental implications that can be raised by this emerging project.